Digital Versus Conventional Impressions - Mohammad Munthir Abdulrazzaq; Mithaq R. Mohammed (Dentistry 3000, 2025)
Objective: The purpose of this research was to compare and contrast, in vivo, the three-dimensional (3D) dental impressions produced by digital and traditional methods. Materials and Methods: This research was comprised of ten individuals who had full natural teeth. The subjects' molars were digitally imprinted using an intra-oral scanner (Helios 600 3D). The double-mix impression method (SILAXIL BOX & PROTESIL LIGHT) was also used to create a silicone imprint. The Lava COS system exported the stereolithography (STL) data immediately, and a three-dimensional (3D) intra-oral scanner recorded the STL data of a plaster model created from a silicone imprint. The 3D assessment program captured the STL files. It overlaid them using the best-fit-algorithm approach for each impression technique (least-squares method, PolyWorks, InnovMetric program). The Wilcoxon signed-rank test was used to compare the two methods with respect to 3D data. Results: Differences between digital impressions were less noticeable when comparing them to silicone impressions, according to a visual analysis of stacked datasets. Using a digital imprint approach yielded more confirmation (0.014± 0.02 mm) compared to a traditional method (0.023 ± 0.01 mm). Conclusion: According to this in vivo investigation, digital impression technology outperforms traditional impression techniques.